Line registration of jittered video - KOKARAM, ANIL CHRISTOPHER (My University, 1997)
With the imminent widespread availability of digital video broadcasts and the subsequent increase in the demand for broadcast material, image sequence restoration is an increasing source of concern for both archivists and broadcasters. This paper presents a two stage technique for registering the lines in video data digitized from a noisy source. In such situations the horizontal synchronization pulses may not have the correct amplitude causing the loss of `lock' in the digitizing apparatus. The effect is that the image lines are randomly shifted horizontally with respect to their true locations. This manifests as jagged vertical edges in the observed sequence, an annoying artefact. The algorithm presented here relies on a two-dimensional autoregressive (2D AR) model of the image to measure the line displacements using a multiresolution scheme
International Conference on Acoustics, Speech and Signal Processing
PUBLISHED
Keywords: Image sequence restoration